2022
DOI: 10.1002/ece3.9069
|View full text |Cite
|
Sign up to set email alerts
|

Empirical and philosophical problems with the subspecies rank

Abstract: Species‐level taxonomy derives from empirical sources (data and techniques) that assess the existence of spatiotemporal evolutionary lineages via various species “concepts.” These concepts determine if observed lineages are independent given a particular methodology and ontology, which relates the metaphysical species concept to what “kind” of thing a species is in reality. Often, species concepts fail to link epistemology back to ontology. This lack of coherence is in part responsible for the persistence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 167 publications
2
28
0
Order By: Relevance
“…However, the significant differences in body sca lation and relative tail length may lead some readers to question whether O. arenarius should be considered a subspecies of O. macrurus instead of a junior synonym. In herpetology, the contemporary application, criteria and usage of subspecies is controversial (Hawlitschek et al 2012;Torstrom et al 2014;Kindler and Fritz 2018;De Queiroz 2020;Hillis 2020;Burbrink et al 2022) and a discussion of its utility is beyond the scope of this pa per. Recent designations of subspecies generally follow the suggestions of Mayr and Ashlock (1991) and Braby et al (2012), who define subspecies as a distinct metapop ulations that are phenotypically diagnosible and are on a trajectory towards evolutionary independence.…”
Section: Discussionmentioning
confidence: 99%
“…However, the significant differences in body sca lation and relative tail length may lead some readers to question whether O. arenarius should be considered a subspecies of O. macrurus instead of a junior synonym. In herpetology, the contemporary application, criteria and usage of subspecies is controversial (Hawlitschek et al 2012;Torstrom et al 2014;Kindler and Fritz 2018;De Queiroz 2020;Hillis 2020;Burbrink et al 2022) and a discussion of its utility is beyond the scope of this pa per. Recent designations of subspecies generally follow the suggestions of Mayr and Ashlock (1991) and Braby et al (2012), who define subspecies as a distinct metapop ulations that are phenotypically diagnosible and are on a trajectory towards evolutionary independence.…”
Section: Discussionmentioning
confidence: 99%
“…Broadhurst (2000) suggested that their two putative taxa were distinct, but because there were additional ‘intermediate’ form(s) possibly derived from hybridisation, the two should be recognised as subspecies (however, this was not formally done). The topic of using the rank of subspecies and its evolutionary relevance has been and continues to be contentious (de Queiroz 2020, 2021; Hillis 2021; Burbrink et al 2022). It has been suggested that the rank of subspecies may be used to denote species that are incompletely separated (de Queiroz 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the continuum between microevolutionary processes and macroevolutionary patterns may be disrupted due to variance in the persistence of populations, a necessary step to be considered as distinct lineages. This variance may be associated with extinction by forces such as environmental change, competition, disease, or hybridization (Burbrink et al, 2022;Raia et al, 2016;Rhymer & Simberloff, 1996;Vonlanthen et al, 2012). It could be argued that additional processes are relevant to prevent extinction via hybridization, such as increasing genomic incompatibilities thus enhancing reproductive isolation (Mayr, 1963;Wolf & Ellegren, 2017;Wu, 2001).…”
Section: Discussionmentioning
confidence: 99%